An FPGA Based Power Quality Monitoring System - Yildirim, Ozal; Eristi, Belkis; Eristi, Huseyin; Unal, Sencer; Erol, Yavuz; Demir, Yakup (Ieee, 2015)
In this study, a new FPGA based monitoring system has been developed for monitoring the power quality. Designed system performs the calculations of power quality parameters on real-time voltages and currents datas that are obtained from the network. FPGA devices that have recently become more popular in digital signal processing field is used in the structure of monitoring system. Designed power quality monitoring system has been established on electrical distribution panels of Tunceli University Vocational Schools. When the obtained test results are evaluated, it has been observed that the proposed power quality monitoring system is successful.
FPGA Tabanli Bir Güç Kalitesi Izleme Sistemi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: power quality; FPGA; signal processin